PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR PPKn DI KELAS V MI MA’ARIF NU SUNYALANGU - Samsudin, Samsudin; Fauzi, Fauzi (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Ngawi, 2023)
Students' performance in civics classes is poor due to the application of methods that prioritise memory. Therefore, a new approach in education is needed, which can motivate students to engage in active learning. Make a Match is one of the interactive learning models used, along with other co-operative learning methods. Unlike the teacher who runs the class through lectures, students actively participate in this learning method. This methodology asks the teacher to create two cards: one card contains an answer and the other card contains a question or problem. The students' task is to find their card pair. In terms of solving problems that arise during learning, using this learning model turns out to be the best solution. Before the Make a Match model was implemented, 58.82% of the students met the requirements for mastery; after this model was implemented, this percentage increased to 94%. The conclusion of this study supports the opinion that Make a Match technique can improve students' academic achievement.